CHALLENGES OF BUSINESS JUDGMENT RULE IMPLEMENTATION AS AN EFFORT TO PROTECT COMPANY DIRECTORS IN INDONESIA - Nur Hasanah, Aida; Hasanah, Uswatun (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
In Indonesia, company executives is frequently held personally liable of any damages incurred through the business. Indeed, an analysis of the BJR reveals that director is afforded protection for their business decisions, as such decisions are seen to be made with the prudence expected of professionals in their capacity. The execution of BJR has been suboptimal in Indonesia. The research seeks to recognize the challenges and issues related to the application within the BJR principle in Indonesia and to determine whether the legal framework for limited liability companies has been comprehensively analyzed concerning the BJR principle as a protective measure for company directors.The study methodology employed is empirical juridical. The findings indicate that the persistent unsatisfactory implementation of the BJR stems from the inadequately detailed regulations concerning the BJR within the law, particularly regarding the constraints of the prudential standard, resulting in challenges in law enforcement.Uncertainty persists regarding the courts' interpretation of the BJR. The challenge in implementing BJR in Indonesia is the insufficient practical comprehension among directors and shareholders who do not fully grasp the concept of BJR. Strict rules impede the flexibility of decision-making by the committees of executives, resulting in conflicts between regulations and business practices.